2006
DOI: 10.1038/nature04623
|View full text |Cite
|
Sign up to set email alerts
|

Type ID unconventional myosin controls left–right asymmetry in Drosophila

Abstract: Breaking left-right symmetry in Bilateria embryos is a major event in body plan organization that leads to polarized adult morphology, directional organ looping, and heart and brain function. However, the molecular nature of the determinant(s) responsible for the invariant orientation of the left-right axis (situs choice) remains largely unknown. Mutations producing a complete reversal of left-right asymmetry (situs inversus) are instrumental for identifying mechanisms controlling handedness, yet only one such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
303
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(315 citation statements)
references
References 27 publications
10
303
0
2
Order By: Relevance
“…Evidence has been presented that nonmuscle myosins function in Drosophila in organizing the cytoskeleton during morphogenesis and in controlling left-right asymmetry (Blake et al, 1998(Blake et al, , 1999Speder et al, 2006). In summary, our study suggests that NMHC-IIB within the cytoskeleton has a role in laterality and mammalian mouse heart morphogenesis during looping.…”
Section: Actomyosin Cytoskeleton and Heart Loopingmentioning
confidence: 51%
“…Evidence has been presented that nonmuscle myosins function in Drosophila in organizing the cytoskeleton during morphogenesis and in controlling left-right asymmetry (Blake et al, 1998(Blake et al, , 1999Speder et al, 2006). In summary, our study suggests that NMHC-IIB within the cytoskeleton has a role in laterality and mammalian mouse heart morphogenesis during looping.…”
Section: Actomyosin Cytoskeleton and Heart Loopingmentioning
confidence: 51%
“…1C and D and Table 1). Spéder et al 13 reported that the laterality of the spermiduct and genitalia in the adult of Myo31DF homozygote was also reversed (review on the roles of Myo31DF in the asymmetry of the adult genitalia www.landesbioscience.com…”
Section: Introductionmentioning
confidence: 99%
“…These findings indicate that Myo95E 1 and Myo95E 2 are null alleles of Myo95E. We used the Myo95E 1 allele in subsequent studies, because it had a larger deletion than Myo95E 2 ( Figure 1C).Myo31DF or Myo61F homozygous mutant flies were previously reported to be viable and fertile (Hozumi et al 2006;Speder et al 2006;Hegan et al 2007). Our finding that the Myo61F 1 or Myo95E 1 homozygotes were also viable and fertile (data not shown) combined with the earlier data suggests that all class I myosins are dispensable for survival in Drosophila, if their functions are disrupted separately.…”
mentioning
confidence: 99%
“…These results demonstrated that class I myosins are not essential for survival itself, but are required for optimal hatching and survival rates, and thus are important mediators in Drosophila, at least under our experimental conditions. Differential expression of Myo31DF, Myo61F, and Myo95E during embryogenesis Myo31DF and Myo61F mRNAs and their protein products are detected in the gut epithelium and genital disc (Morgan et al 1995;Hozumi et al 2006;Speder et al 2006;Petzoldt et al 2012). To gain insight into the tissue-specific roles and functional redundancy of the three class I myosins in the LR asymmetric development of the embryonic gut, we analyzed their expression in embryos, using in situ hybridization.…”
mentioning
confidence: 99%